Histórias do Brasil: uma análise de letras da Banda Armahda (2013 – 2015) - Pinto, Leila Cristiane Rodrigues (2024)
This work proposes the relationship between History and Music, based on the analysis of lyrics by the band Armahda, highlighting the capacity of this union as a means of disseminating historicity and expressing cultural identity. Musical productions can play a role in the construction and dissemination of historical narratives, moving themes and contributing to the understanding of different subjects. In this context, we seek to connect History and Music, exploring the analysis of song lyrics by the Brazilian group Armahda, published between 2013 and 2015. To achieve this purpose, we will use Discourse Analysis - the field of Linguistics, as an analytical methodology for musical lyrics, applying the work Discourse Analysis: principles and procedures - Eni P. Orlandi. The basis for History and Music comes from the books: Years of Lead: rock and repression during AI-5 - Alexandre Saggiorato; History and Music: using music as a historical source - Icles Rodrigues. The Dictionary of Historical Concepts - Kalina Vanderlei Silva and Maciel Henrique Silva, corroborated the writing of this research, providing us with support for the definition of meanings pertinent to the construction of this study. By examining the discourse present in these lyrics, we seek to understand how music can be a vehicle for transmitting historical and cultural perspectives, thus enriching society's understanding of its own past and identity.